An Overview of Aquatica Fu et al., a Phylogeny of Aquatic Fireflies Using Mitochondrial Genomes, a Description of Two New Species, and a New Record of Aquatic Fireflies in China (Coleoptera: Lampyridae: Luciolinae) - Xinhua Fu; Lesley Ballantyne (Insects, 2024)
There are now seven species in the genus Aquatica Fu & Ballantyne, with all but one known from the characteristics of males, females, and larvae. Molecular information is combined with morphological taxonomy for the delimitation of both genus and species. The monophyly of the genus Aquatica is strongly supported in six trees, and its position as sister to the genus Nipponoluciola Ballantyne Kawashima Jusoh et Suzuki is stable across maximum likelihood and Bayesian inference results. Two new species of Aquatica Fu & Ballantyne, A. qingshen sp. nov. and A. xianning sp. nov., described from the features of males, females, and larvae, are closely related within a single clade within the genus Aquatica. Females have distinctively shaped median oviduct plates. A Chinese population identified as A. lateralis was found to be morphologically similar to the Japanese population, but genetic distances suggest that it is a distinctive species. No larvae are associated with this species. Definitions of the aquatic status of Luciolinae fireflies are expanded.